ЗАСТОСУВАННЯ АСИНХРОННОГО ЕЛЕКТРОПРИВОДУ З КЕРУВАННЯМ ЗА РЕАКТИВНОЮ ПОТУЖНОСТЮ - Чепкунов, Р.А. (Інститут електродинаміки НАН України, Київ, 2023)
The practical issues of using an asynchronous electric drive with reactive power control with ensuring the independence of the load and over load capacity from changes of induction motor parameters, uninterrupted diapason of speed regulation, including zero, fast regulation and simplification of the microprocessor control system are considered .It is show what it may be to implement. References 8, figures 6.